Overview and status of the Long-Baseline Neutrino Facility Far Site cryogenics system. Issue 1 (1st May 2022) - Montanari, D; Adamowski, M; Bremer, J; Delaney, M; Doubnik, R; Freitag, J; Haaf, K; Nichols, T; Parchet, A; Young, I
Abstract: The Sanford Underground Research Facility (SURF) will host the Far Detector of the Deep Underground Neutrino Experiment (DUNE), an international multi-kiloton Long-Baseline neutrino experiment that will be installed about one and a half kilometers underground in Lead, SD. Detectors will be located inside four cryostats filled with almost 70, 000 metric tons of ultrapure liquid argon, with a level of impurities lower than 100 parts per trillion of oxygen equivalent contamination. The cryogenics infrastructure supporting this experiment is provided by the Long-Baseline Neutrino Facility (LBNF). This contribution presents modes of operation, layout, and main features of the LBNF Far Site cryogenic system, which is composed of three subsystems: Infrastructure, Proximity, and Internal cryogenics. The Infrastructure cryogenics supports the needs of the cryostat and Proximity cryogenics. It includes the equipment to receive the argon in liquid phase, vaporize it and transfer it underground as a gas, the nitrogen system (composed of the refrigeration system, liquid nitrogen buffer tanks and liquid and gaseous nitrogen distribution), liquid and gaseous argon distribution and process controls. The Proximity cryogenics receives fluids from the Infrastructure cryogenics and delivers them to the Internal cryogenics at the required temperature, pressure, purity and mass flow rate. It includes the argon condensers, liquid and gaseous argon purification and regeneration systems, nitrogen and argon phase separators, piping, valves, and instrumentation. The Internal cryogenics comprises the liquid and gaseous argon distribution inside the cryostats for the commissioning, cool down, fill, and steady state operations of the cryostats and detectors. An international engineering team is designing these systems and will manufacture, install, commission, and qualify them. This contribution describes the main features, performance, functional requirements, and modes of operation of the LBNF Far Site cryogenics system. It also presents the status of the design, along with present and future needs to support the DUNE experiment.